2015
DOI: 10.1002/aic.15118
|View full text |Cite
|
Sign up to set email alerts
|

Amine‐functionalized mesoporous silica: A material capable of CO2 adsorption and fast regeneration by microwave heating

Abstract: WileyNigar, H.; García-Baños, B.; Penaranda-Foix, FL.; Catalá Civera, JM.; Mallada, R.; Santamaria, J. (2016). Amine-functionalized mesoporous silica: A material capable of CO2 adsorption and fast regeneration by microwave heating. AIChE Journal. 62 (2) The surface of ordered mesoporous (MCM-48) silica has been subjected to covalent grafting with silane molecules containing one to three amino groups. The dielectric properties of the materials were studied in detail, and the functionalized materials were used f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(33 citation statements)
references
References 35 publications
0
30
0
Order By: Relevance
“…Inserting alkaline amine groups into adsorbents can improve CO 2 chemisorption, which can be normally achieved in three routes: amines anchored to the supports in the form of covalent bonds, 24,25 amines impregnated into the inner channel of supports 26,27 and amine containing polymers introduced directly without second modication by molecular imprinting technology. 28,29 In the rst route, the graed amines are usually aminosilanes.…”
Section: Introductionmentioning
confidence: 99%
“…Inserting alkaline amine groups into adsorbents can improve CO 2 chemisorption, which can be normally achieved in three routes: amines anchored to the supports in the form of covalent bonds, 24,25 amines impregnated into the inner channel of supports 26,27 and amine containing polymers introduced directly without second modication by molecular imprinting technology. 28,29 In the rst route, the graed amines are usually aminosilanes.…”
Section: Introductionmentioning
confidence: 99%
“…Many porous materials (e.g., zeolites, carbons, and silica) have been developed for CO 2 capture. Among them, N‐doped porous carbons (NPCs) have received much attention because of their low cost, high porosity, and good chemical and thermal stability .…”
Section: Introductionmentioning
confidence: 99%
“…Nigar et al focused on CO 2 desorption from a functionalized mesoporous silica reporting a significant reduction in desorption time when switching from conventional heating to microwave heating. Moreover, the authors also found no changes in the adsorption capacity of the amino-functionalized material after 20 adsorption-regeneration cycles [199].…”
Section: Environmental Catalysismentioning
confidence: 97%